A Model of Relationships between Personality Traits and Academic Self-Handicapping: The Mediating Role of Achievement Goals - Fariba Tabe Bordbar; Ahmad Rastegar (مجله ایرانی آموزش در علوم پزشکی, 2015)
Introduction: Identifying factors affecting academic self-handicapping as a psychological harm and a strategy to justify probable academic failure in the future has undesirable educational consequences. Thus, the purpose of this study was to provide a model to predict academic self-handicapping on the basis of personality traits and achievement goals. Methods: This descriptive-correlational study was performed on 258 students of nursing school in Shiraz University of Medical Sciences in 2014. Participants were selected through stratified sampling. The subjects answered to a self-report questionnaire measuring achievement goals, personality traits, and academic self-handicapping. Data were analyzed using path analysis in LISREL software. Results: Findings showed that indirect effects of extroversion, task-orientation, agreeableness and openness to experience on academic self-handicapping were all significant at -0.08, -0.11, and -0.07 respectively (p<0.01). Also, the indirect effect of agreeableness on academic self-handicapping was 0.03 and significant (p<0.05). The indirect effect of neurosis on academic self-handicapping, unlike other personality traits, was positive (0.10) and significant (p<0.01). Based on findings, RMSEA equaled 0.06, CFI equaled 0.98, GFI equaled 0.99, AGFA equaled 0.94, and x2/df ratio equaled 2.68 which all indicate a good-fitting model. Conclusion: The results showed that implementation of personality measures in educational settings and deeper understanding of the inner characteristics of learners might keep them away from exposure to psychological harms such as academic self-handicapping.